2011
DOI: 10.1007/s11095-011-0414-9
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Aggregation and Immunogenicity in Biotherapeutics: T- and B-Cell Immune Epitopes May Contain Aggregation-Prone Regions

Abstract: Biotherapeutics, including recombinant or plasma-derived human proteins and antibody-based molecules, have emerged as an important class of pharmaceuticals. Aggregation and immunogenicity are among the major bottlenecks during discovery and development of biotherapeutics. Computational tools that can predict aggregation prone regions as well as T- and B-cell immune epitopes from protein sequence and structure have become available recently. Here, we describe a potential coupling between aggregation and immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 46 publications
(86 reference statements)
1
64
0
Order By: Relevance
“…Macromolecular aggregates are one of several potential risk factors for adverse immunogenic responses to biotherapeutic drugs. 4,5 Moreover, aggregation might lead to a decrease in biotherapeutic activity, and has implications for regulatory approval and delivery methods.…”
Section: Introductionmentioning
confidence: 99%
“…Macromolecular aggregates are one of several potential risk factors for adverse immunogenic responses to biotherapeutic drugs. 4,5 Moreover, aggregation might lead to a decrease in biotherapeutic activity, and has implications for regulatory approval and delivery methods.…”
Section: Introductionmentioning
confidence: 99%
“…The immunogenicity studies indicated that Sak(E80C-PEG) had greatly reduced immunogenicity in guinea pigs. Some researchers thought that immunogenicity of protein was associated with protein aggregate [26]. However, aggregates of Sak(E80C-PEG) were not observed in either SDS-PAGE or SEC-HPLC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is desirable to use in silico or in vitro human cell-based assessments for the immunogenicity prediction, including predictions of aggregation prone regions and T and B cell epitopes. To this end, Kumar et al described the importance of investigating the impact of aggregation on immunogenicity and potential coupling of T and B cell epitopes and aggregation-prone regions (61). Computational tools that can predict aggregation prone regions as well as T-and B-cell immune epitopes from protein sequence and structure have become available recently from several commercial vendors (58,(62)(63)(64).…”
Section: In Vitro Predictive Tools For Immunogenicitymentioning
confidence: 99%